Modeling And Cost Planning For The Tanjungpandan District Court Building Project Using Building Information Modeling (BIM) Method - Ahmad Yudi; Mohammad Ihsan Firmansyah; Kirtinanda P.; Ayu Sinta Aprilia; Siti Rahma (Universitas Islam Raden Rahmat, Malang, 2025)
Infrastructure development in Indonesia is currently in a fairly massive development phase. To support this, the government of the Republic of Indonesia improves the quality of national development by continuing to adapt to existing technological developments, one of which is Building Information Modeling (BIM). In this case, the use of BIM in planning and designing a construction object becomes easier because it can be done simultaneously. In addition, the design produced through the BIM method also contains data and information that can be used in other phases of construction. One of the data produced is the quantity of materials that can be used to estimate construction costs. In this study, the use of the BIM method is intended to determine the comparison of the costs generated to the cost of conventional methods of the project. The results of the cost calculation obtained by the BIM method are cumulatively -2,06% lower than the conventional method. There is a varying cost deviation for each work item, with the smallest cost deviation being +0,48% for beam structure work and the largest cost deviation being +126,26% for stair work.